Associations between neurolinguistic deficits and personality traits in people with epilepsy - Floros, Nikitas; Papagiannakis, Nikolaos; Kyrozis, Andreas; Chroni, Elisabeth; Polychronopoulos, Panagiotis (Frontiers in Neurology, 2024)
Intro: People with epilepsy (PWE) have been hypothesized to have higher prevalence of personality disorders and cognitive disorders. The objective of this study was to investigate the controversial notion of "epileptic personality", a series of supposedly specific personality traits of people with epilepsy (PWE). Methods: For this purpose, 29 individuals with Mesial Temporal lobe Epilepsy (MTLE) and 23 with Juvenile myoclonic epilepsy (JME) as confirmed by electroencephalography (EEG), MRI scans and clinical examination, underwent a thorough neuropsychological and personality assessment. The resulting neuropsychological profiles were statistically analyzed considering possible personality disorders, character traits, cognitive and linguistic deviations from 20 healthy controls (HC). Results: Our findings suggest accumulative cognitive and linguistic deficits in individuals with epilepsy compared to controls. It is possible that these might be misinterpreted as personality disorders. Specifically, personality traits (p=0.049) and verbal fluency (p=0.013), were significantly different between PWEs and controls. Also, the type of epilepsy and lateralization seem to affect executive function (p=0.049) and pragmatology scores (p<0.001), exhibiting differences in subgroup analysis. Discussion: Different theories are considered as plausible pathophysiological explanations for the aforementioned differences. This research might serve as a basis to further investigate the cognitive aspects of epilepsy and possible pharmacological interventions, which are currently lacking.